The continuous training in the development of Nursing teacher competencies in higher education in Portugal - Ferrinho Ferreira, Rogério Manuel; Cubo Delgado, Sixto; Jesus Carioca, Vito José (Revista Complutense de Educación, 2019)
The main goal of this investigation is to analyse the importance given to the continuous training on the development of professional skills in higher education professors, engaging the professors from public education that provide Nursing training in Portugal. A descriptive methodology was used, based on the application of a questionnaire to a sample of 157 teachers selected through a simple random sampling. Content validity of the questionnaire was obtained through consultation with experts. The reliability of the measuring instrument was obtained with the Cronbach alfa coefficient in the categories “Motivations for engagement training actions and/ or continuous professional development”, “Continuous training present needs” and in the dimension “Emphasis placed on the continuous training in the development of higher education professor skills”. The results indicate the existence of a relationship between the teachers needs and their motivations, the importance attributed to the continuous training in the development of competences and there is also a significant difference between the importance attributed by the teachers to the continuous training, category “Investigate” and the other categories of skills.
Keywords: continuous training; teacher; motivation; training need; professional skills